2009
DOI: 10.1093/nar/gkp1109
|View full text |Cite
|
Sign up to set email alerts
|

A new type of IRES within gag coding region recruits three initiation complexes on HIV-2 genomic RNA

Abstract: Genomic RNA of primate lentiviruses serves both as an mRNA that encodes Gag and Gag-Pol polyproteins and as a propagated genome. Translation of this RNA is initiated by standard cap dependant mechanism or by internal entry of the ribosome. Two regions of the genomic RNA are able to attract initiation complexes, the 5′ untranslated region and the gag coding region itself. Relying on probing data and a phylogenetic study, we have modelled the secondary structure of HIV-1, HIV-2 and SIVMac coding region. This app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(105 citation statements)
references
References 54 publications
2
103
0
Order By: Relevance
“…Actually, we attributed the genetic instability of a recombinant YF virus expressing a fragment of the SIV Gag precursor protein to the presence of an IRES element localized at the 3′end of gene encoding the SIV Matrix protein. 69 We managed to substantially improve the genetic stability of this recombinant YF17D virus by introducing mutations in the IRES element. 70 The foreign antigens expressed by the recombinant YF17D virus in the E/NS1 region appear to remain cell-associated as described elsewhere.…”
Section: Expression Of Larger Fragments By the Yf17d Virusmentioning
confidence: 99%
“…Actually, we attributed the genetic instability of a recombinant YF virus expressing a fragment of the SIV Gag precursor protein to the presence of an IRES element localized at the 3′end of gene encoding the SIV Matrix protein. 69 We managed to substantially improve the genetic stability of this recombinant YF17D virus by introducing mutations in the IRES element. 70 The foreign antigens expressed by the recombinant YF17D virus in the E/NS1 region appear to remain cell-associated as described elsewhere.…”
Section: Expression Of Larger Fragments By the Yf17d Virusmentioning
confidence: 99%
“…Previous studies on HIV-2 translation have suggested that the genomic RNA contains an IRES located downstream from the gag AUG1 initiation codon (Herbreteau et al 2005;Weill et al 2010). According to this model, HIV-2 IRES recruits ribosomes for translational initiation at AUG1 and farther downstream at AUG2 and AUG3 to generate the three Gag isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Ohlmann and coworkers have shown that these three isoforms of Gag are expressed during HIV-2 infection, which they attributed to alternative initiation events (Herbreteau et al 2005;Weill et al 2010). The first isoform, p58, initiates synthesis from a start codon located at nucleotides 546-548 (AUG1).…”
Section: Effects Of Artificially Evolved C-box and G-box Sequences Onmentioning
confidence: 99%
“…Some researchers consider such 5'-UTR IRESes as sufficiently different from the bona fide inter-cistron IRESes to warrant them a special name, cap-independent translational enhancers (CITEs) [17]. Some CITEs appear to be reasonably efficient, attracting up to three translation initiation complexes on a single mRNA [18]. It is difficult to define a specific sequence motif for CITEs and they are presumed to act through secondary structures.…”
Section: Use Of Non-canonical Mrnas As Gene Vectorsmentioning
confidence: 99%